The High Risk of Postintubation Tracheal Stenosis in Patients Intubated for Organophosphate Poisoning - Başoǧlu, A.; Taslak Şengül, A.T.; Kefeli, M.; Yetim, T.D.; Bekdemir, O.S.; Kutlu, T. (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2012)
Background: This study aims to reevaluate patients who developed postintubation tracheal stenosis with regard to the primary reason for intubation and therapy. Methods: Between January 2001 and December 2006, 14 of 230 patients who underwent endotracheal intubation for various reasons in the intensive care unit (ICU) and then developed postintubation tracheal stenosis were analyzed retrospectively. All patients were examined with a neck and chest computed tomography (CT) scan, and tracheal anastomosis was performed. The resected stenotic tracheal rings were evaluated histopathologically. Results: A total of 201 patients underwent endotracheal intubation due to general trauma (GT), and 29 of these were due to organophosphate poisoning (OPP). Fourteen of these patients developed tracheal stenosis, including nine with OPP and five with GT. The medical therapy and care were generally similar in both groups, except that high doses of atropine and/or pralidoxime were administered to the OPP patients. Diffused chronic active inflammation, fibrosis, and epithelial loss in the resected stenotic tracheal rings were more common in the OPP group than in the GT group. Conclusion: The primary cause of intubation and the medical therapy employed may have an effect on postintubation tracheal stenosis.
Keywords: Intensive Care; Postintubation; Tracheal Stenosis; Tracheal Surgery